2020
DOI: 10.1111/spol.12681
|View full text |Cite
|
Sign up to set email alerts
|

In the eye of the stormagain! Social policy responses to COVID‐19 in Southern Europe

Abstract: This paper aims to describe and discuss the significance of the social policy measures implemented in Southern European countries—Greece, Italy, Portugal and Spain—in response to the first wave of COVID‐19. Our analysis covers interventions from 1 March to June 30, 2020. Despite significant differences in how the COVID‐19 pandemic spread—with Italy and Spain experiencing much higher rates of infection and lethality—Southern European economies are among the most hard‐hit—and are likely to find themselves in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 6 publications
1
43
0
1
Order By: Relevance
“…In Italy, Galasso (2020) observed adverse effects on blue collars, low-educated workers and low-income services workers as well. Social distancing implied more significant job losses among ethnic minorities in the United States, especially Hispanics (Béland et al, 2020;Montenovo et al, 2020). Layoffs in the United States exacerbated pre-existing forms of parental status and gender inequality in employment, with a consistent fatherhood premium (Dias et al, 2020).…”
Section: Shutdown Sectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Italy, Galasso (2020) observed adverse effects on blue collars, low-educated workers and low-income services workers as well. Social distancing implied more significant job losses among ethnic minorities in the United States, especially Hispanics (Béland et al, 2020;Montenovo et al, 2020). Layoffs in the United States exacerbated pre-existing forms of parental status and gender inequality in employment, with a consistent fatherhood premium (Dias et al, 2020).…”
Section: Shutdown Sectorsmentioning
confidence: 99%
“…In conclusion, the more fragile workers were more likely to stop working and to suffer immediate income loss from the social distancing measures that affected mostly low-skilled services sectors (Blundell et al, 2020;Galasso, 2020). The variance in job losses in terms of demographic characteristics depends on the sorting between different sectors (Montenovo et al, 2020): the affected sectors showed a predominance of youth, minorities, women and low-skilled workers, usually employed with temporary contracts or in precarious working conditions, including solo self-employment.…”
Section: Shutdown Sectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This factor has led to the exhaustion of Portuguese society in general. Observing the pandemic phases in Portugal, the adoption of restrictive measures to ensure a low number of infected people was essential in the first wave [7]. Nevertheless, the speed of taking measures was not so evident in the subsequent waves.…”
Section: Discussionmentioning
confidence: 99%
“…Portugal is now at the end of its third wave, which started right after the Christmas and New Year celebrations of 2020. In the first wave of COVID-19, in March 2020, the measures adopted managed to contain the spread of the pandemic, and we believe that this is mainly due to the quick response adopted by the government, which approved the lockdown at an early stage of the pandemic [7]. However, the first wave was followed by a second wave that started in September 2020.…”
Section: Introductionmentioning
confidence: 99%